Experimental study on the strengthening mechanism of carbon fiber-reinforced sand powder 3D-printed rock-like materials - Lishuai Jiang; Xin He; Ye Zhao; Pimao Li; Yang Zhao; Zongke Wang; Dingrui Guo; Qi Gu (Case Studies in Construction Materials)
Sand powder 3D printing has proven to be one of the most effective methods for replicating the physical and mechanical properties of natural rock. However, its limitations in the strength and stiffness of the printed materials hinder its potential for hard rock simulation. Carbon fiber, which is known for its high modulus and tensile strength, is widely used in concrete reinforcement. In this study, silica sand and furan resin were selected as printing materials, and carbon fiber at various dosages were incorporated during the preparation process. Uniaxial compression and Brazilian splitting tests were conducted on the treated specimens to evaluate the impact of carbon fiber on their macroscopic mechanical properties. In addition, acoustic emission monitoring and scanning electron microscopy were used to investigate the microscopic mechanisms involved. The results demonstrate that the added carbon fiber effectively inhibits crack initiation and propagation, significantly enhancing the stressstrain curve, uniaxial compressive strength, elastic modulus, and peak strain of the specimens. Regarding the brittleness index, carbon fiber allows reproduction of natural rocks, excluding schist. On a microscopic level, carbon fibers provide physical reinforcement through a ''binder + carbon fiber'' bridge structure, which greatly improves the toughness and tensileshear resistance of the specimens. However, excessive carbon fibers can lead to the formation of weak interfaces, ultimately compromising the overall mechanical properties. This study offers new insights into enhancing the strength and stiffness of sand powder 3D-printed rock-like specimens, broadening their applicability in laboratory tests and advancing the use of 3D printing in rock mechanics and engineering.